Modifiable life style factors and male reproductive health: a cross-sectional study in IVF clinic attendees in Ghana - Brodrick Yeboah Amoah; Saliah Yao Bayamina; Cosmos Gborsong; Hubert Owusu; George Awuku Asare; Emmanuel Kwabena Yeboah; Josephine Ablakwa; Georgina Hammond (Frontiers in Reproductive Health)
BackgroundMale infertility is a significant global public health issue, with modifiable lifestyle factors such as smoking, obesity, and psychological stress contributing to impaired semen quality and hormonal dysregulation. This study investigates the relationships between modifiable lifestyle factors, reproductive hormones, and semen quality in Ghanaian males attending an IVF clinic.MethodsA cross-sectional study was conducted with 212 male participants recruited from a fertility clinic in Ghana. Lifestyle factors were assessed using standardized questionnaires, and semen samples were analyzed following WHO guidelines. Hormonal profiles (LH, FSH, testosterone, estradiol) were measured using the enzyme-linked fluorescent assay (ELFA). Statistical analyses included Pearson's product-moment correlation and Bonferroni correction.ResultsSmoking and psychological stress were significantly associated with reduced sperm motility, viability, and concentration (p < 0.05). Elevated BMI correlated negatively with sperm concentration and testosterone levels (p < 0.05). Alcoholic bitters was linked to decreased semen quality, while caffeine consumption showed a positive association with progressive sperm motility.ConclusionModifiable lifestyle factors, such as smoking, psychological stress, and increased body mass index (BMI), play a crucial role in male reproductive health by adversely affecting semen parameters and hormonal balance. These findings emphasize the need for public health interventions targeting modifiable behaviors to improve fertility outcomes.